INTRODUCTION TO W.E.B. DU BOIS - Wright, Earl, II; Ojeh, Kalasia S. ([S.l.] : ROUTLEDGE, 2024)
An Introduction to W. E. B. Du Bois examines the historical contributions to social science and the continuing relevance of the work of W. E. B. Du Bois in an accessible manner. The first volume of its kind, it places the theories of Du Bois in context, showing how the socioracial environment in which he grew up and came of age influenced the development of his thought. In addition to covering wellknown concepts such as double consciousness, the veil, and religious fatalism, the authors discuss Du Bois' uncoined theories emanating from the Atlanta University Studies, as well as his contributions to the development of Black sociology and research methodology. A groundbreaking contextualization and summary of the importance of Du Bois' work to sociology and sociological theory, this book constitutes a muchneeded resource for scholars and students seeking to understand this scholar's significance to the social sciences beyond the elementary level.
Keywords: Du Bois, W. E. B. -- 1868-1963.; African American sociologists -- Biography; United States -- Race relations -- History; SOCIAL SCIENCE / General; SOCIAL SCIENCE / Sociology / General